Comparison of oral and intravenous fluid therapy in newborns with hypernatremic dehydration. (March 2014) - Erdemir, Aydin; Kahramaner, Zelal; Cosar, Hese; Turkoglu, Ebru; Kanik, Ali; Sutcuoglu, Sumer; Ozer, Esra Arun
Abstract Objective: To evaluate the efficacy and complications of oral and intravenous fluid therapy in newborns with hypernatremic dehydration. Methods: A total of 75 term and near-term (>35 weeks) neonates with hypernatremic dehydration (Na ≥ 150 mmol/L) were included in this retrospective study. The patients were divided into two groups according to therapy approach for rehydration (breast milk-oral formula and intravenous fluid). The decline in sodium concentration (<0.5 mmol/L/h was regarded as safe drop) and complications were analyzed. Results: The mean gestational age, birth weight and age at admission were 38.9 ± 1.4(36–42) weeks, 3341 ± 504 (2500–4500) gram and 4.3 ± 2.6 (1–17) day, respectively. Fever (61.8%) and jaundice (39.4%) were the most common presenting signs. Forty-four (58.6%) of the infants were treated with breast milk and/or oral formula (group 1) and 31 (41.4%) of the infants were treated with IV fluid (group 2). In group 1 and group 2, respectively, mean % weight loss, 5 and 7.5; median serum sodium at admission, 153 and 152 mmol/L; median change in sodium at 12 hours, 7 and 11 mmol/L; and median change in sodium at 24 hours, 10 and 15 mmol/L. The decline in sodium concentration was more safely in group 1 than group 2 at both 12 and 24 hours of rehydration. One patient had convulsion associated with cerebral edema in group 2. Otherwise no complication was observed in both groups. Conclusion: Enteral route for fluid replacement may be safe and effective and may be an alternative to intravenous fluid therapy in newborns with hypernatremic dehydration when clinical situation is stable.